The (academic) chair: Embodied relations of arrival, place, and hospitality - Vachhani, Sheena J.; Bell, Emma (The Review of education/pedagogy/cultural studies, 2024)
In this paper we move from considering the chair as an (inanimate) object, to exploring its vitality through a more vibrant and active reading of this inescapable everyday item. We are inspired by feminist new materialism and how affect shapes our understanding of matter. Reading matter in this way surfaces our orientations toward everyday items that show embodied practices of mattering. This, in turn, shines light on how we imbue objects with meaning, and how objects exceed these designations and categorisations to form new unbounded relations with the world. We focus on affective and symbolic meanings to consider different types of chairs, the spaces they occupy, and who comes to sit in them. For example, the empty chair expects an arrival; the occupied chair raises questions related to place and hospitality. Exploring whose bodies occupy an academic chair enables us to understand our embodied relationships with objects and work. We use personal experiences to engage in acts of experimental writing, reflecting on our lived experiences, and combining philosophical musings that bring the chair to life. By re-thinking our relationships to chairs, we invite the reader to resist the urge to dismiss them as mundane pieces of furniture worthy of only function or dismissal, and instead foster an openness that expands consideration of the material relations that travel across bodies and nonhuman kin.